Brazilian Agriculture: Is it all about the Large Farms? - Helfand, Steven M.; Rada, Nicholas E.; Magalhaes, Marcelo M. [UNESP] (Wiley-Blackwell, 2017)
Too often Brazil's agricultural sector is associated primarily with farms operating thousands of hectares in the vast savannah known as the cerrado. Our purpose is to demonstrate that this association is inaccurate, that there exists enormous heterogeneity within the sector across farm sizes. To this end, we separately examine how 1985-2006 total factor productivity (TFP) growth and 2006 production scale vary over farm sizes. We draw on microdata from Brazil's agricultural censuses, aggregated into five farm size classes at the municipality level. While TFP growth has been high on the largest farms, it has been slightly higher on the smallest farms. And when attention is restricted to the 9.5 per cent of farms that accounted for 86 per cent of total production value - those that we designate as 'large scale' - it is clear that most were small and medium-sized farms located in the South and Southeast. Taken together, these results indicate that Brazil's agricultural success has not been only about the large farms. As scholars and policymakers debate the costs and benefits of replicating Brazil's 'Agricultural Miracle' in other parts of the world, it is critical not to overlook the contributions of small and medium-sized farms.